INTERNAL MORAL RESILIENCE AND INSTITUTIONAL INTEGRITY: A DUAL-PILLAR MINDSET OF ANTI-CORRUPTION BEHAVIOR IN INDONESIA - Ardi Ardi; Yohana FCP Meilani; Sylvia Samuel; Margaretha Pink Berlianto (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
Corruption persists in many emerging democracies despite institutional reforms and legal enforcement mechanisms. This study develops and empirically tests a Dual-Pillar Mindset integrating internal moral resilience and external Institutional Integrity Systems safeguards as complementary predictors of corruption resistance intention in Indonesia. This study employed a qualitative literature-based approach through secondary data analysis. The research relied on existing academic sources and theoretical frameworks to construct a proposition conceptual and analytical model. The results indicate that Ethical Leadership positively influences Internal Moral Resilience, and Corruption Resistance Intention, exceeding the direct effect of Institutional Integrity Systems positively influences Corruption Resistance Intention. Furthermore, Internal Moral Resilience positively influences Corruption Resistance Intention and mediate the relationship between Ethical Leadership and Corruption Resistance Intention, producing a synergistic effect. Findings suggest that sustainable anti-corruption reform requires synergy between Ethical Leadership based, Moral Resilience, and Institutional Integrity Systems mechanisms.